In the Shadow of Slavery: Africa’s Botanical Legacy in the Atlantic World - Rucinska, Karolina (The International Journal of Sociology of Agriculture and Food, 2015)
I simply could not put this book down and wished it never to end! This review explains why it was the case for me and might be for many others who will read this academic work. Judith Carney and Richard Nicholas Rosomoff have done an extraordinary job in achieving exactly what they set out to do: to inform the reader on Africa’s botanical legacy; to re-evalute the perception of the African continent’s past and its people, based on the information provided; and to contribute to classical literature on Colombian Exchange by addressing the active role of enslaved people and plants within it. In 10 chapters the authors take the reader on a journey through time and space in order to show how Africa’s botanical world, with its displaced people, animals, plants, knowledge and skills, transformed and contributed significantly to the world in which we live. Thanks to their attention to historical records, oral accounts, linguistics, archaeology, biology and ecology these authors not only provide evidence to support the claim on Africa’s botanical legacy, they also re-evaluate academic contributions on the topic. Having said that, this book has the potential to impact on the ways we relate – culturally, politically, economically, and intellectually – to all of the so far uncredited, unwillingly dislocated human and non-human actors who have shaped the world we share.